Analisis Preminery Research Phase Sebagai Dasar Pengembangan Penuntun Praktikum Biologi Berbasis Pendekatan Saintifik - Mariyana Mariyana; Nurul Fauziah (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
Analysis of the preliminary research phase as the basis for developing a biology practicum guide based on a scientific approach. The purpose of this study was to describe the initial research stage data obtained as a basis for developing teaching and learning materials based on research results that will be made in the future. The development model applied in this study is the Plomp model, which has reached the initial data investigation stage. Instruments for collecting data include interviews, observations, and questionnaires. The results of the student needs questionnaire revealed that students agreed that it was necessary to develop a practicum guide based on a scientific approach with a percentage of 94.73%. The teaching materials that have been used in learning are less effective so that students are less able to understand the subject matter. So it can be concluded that it is necessary to develop teaching materials for practicum guides based on a scientific approach on the material of the circulatory system and respiratory system in class XI SMAN 15 Pekanbaru.